Fetal cardiac anomalies – antenatal detection rates and perinatal outcome data over a 3 year period at heart of England NHS Trust. (18th April 2012) - Arlidge, M; Mukherjee, A; Mupanemunda, R; Patni, S
Abstract : Background: Antenatal detection rates for fetal cardiac anomalies are difficult to ascertain. A 50% detection rate for major cardiac anomalies was acceptable before introduction of outflows tract as part of mid trimester scanning. Method: Comprehensive retrospective data collection using multiple sources, including fetal medicine and neonatal databases, and maternity information system. Patients were identified via local fetal medicine referral criteria and cross-referenced against the West Midlands Perinatal Institute. Perinatal data was obtained and cross-referenced against records at the tertiary referral centre, Birmingham Children's Hospital. 267 mothers were identified between August 2007 to July 2010 (36 months) and details inputted to a purpose built Access database. Data was obtained on risk factors, time of diagnosis, cardiac defect, fetal cardiologist referral and diagnosis, and outcomes including, karyotyping, terminations, gestation and mode of delivery, postnatal diagnosis, surgery, and mortality. Result: Antenatal detection rates depended on the exclusion criteria applied and ranged between 48% when minor anomalies were included, to up to 60% if only major anomalies were considered and 72% if outflow-only anomalies were also excluded. Main diagnoses missed were isolated ventriculoseptal defects (24), transposition of the great ateries (8), pulmonary stenosis (7) and Tetralogy of Fallot (5). Conclusion: Our current detection rates are above satisfactory. Mandatory screening of outflow tracts as part of Fetal Anomaly Screening Programme guideline should lead to improved antenatal detection rates. These had not been introduced at the time this data was collected. A follow-up audit should show improved antenatal detection rates.